Եղեռնից մազապուրծ գաղթականութեան նորայայտ լուսապատկերների եւ գեղանկարչական աշխատանքների ընդհանրութիւնները - Թաջարեան, Իվէթ; Մխիթարեան, Անի (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В начале 20-го века насильственное перемещение армян с их исторической родины заставило многих искать убежища в Святой Эчмиадзине. Здесь также собрались армянские художники, которые поддерживали беженцев своими творческими начинаниями, используя такие инструменты, как камеры и кисти. Недавние открытия стеклянных фотонегативов в Матенадаране выявили поразительные параллели с работами армянских художников 20-го века. Эти фотографии часто служили в качестве ссылок, помогая художникам завершать незаконченные произведения. И фотографии, и картины являются историческими документами, рассказывающими об одежде, ювелирные изделия и мастерство той эпохи. Эта уникальная коллекция представляет собой важный ресурс для культурологии, истории искусств и этнографии. At the beginning of the 20th century, the forced displacement of Armenians from their historical homeland led many to seek refuge in Holy Etchmiadzin. Among them were Armenian artists who supported the refugees through their creative endeavors, employing tools such as cameras and brushes. Recent discoveries of photographic glass negatives in the Matenadaran reveal striking parallels with the works of 20th century Armenian painters. These photographs often served as references, aiding artists in completing unfinished pieces. Together, the photographs and paintings serve as valuable historical records, shedding light on the clothing, jewelry, and craftsmanship of the era. This unique collection represents a significant resource for cultural studies, art history, and ethnography
Keywords: Պատմութիւն